Vegetation monitoring at Pueblo Chemical Depot: 1999-2010 - Rondeau, Renée Jane, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2013)
In 1998 the U. S. Fish and Wildlife Service (USFWS) contracted the Colorado Natural Heritage Program to set up a long-term vegetation monitoring program on U.S. Army Pueblo Chemical Depot (PCD) in Pueblo County, Colorado. The monitoring program was established to detect vegetation changes in shortgrass prairie, sandsage shrubland, and greasewood shrubland as a result of the removal of cattle grazing in 1998. Each vegetation type included areas with four different historic cattle grazing regimes: 1) grazed year-round until 1998, 2) grazed, but not year-round, until 1998, 3) grazed lightly (several times/year) since 1942, and 4) ungrazed since 1942. For the purpose of this study I consider the first two regimes grazed and the latter two regimes ungrazed All further reference to the grazed regime refers to its historical use prior to 1998. During the 1999-2010 years of monitoring neither grazed nor ungrazed study plots discussed in this report received any livestock grazing.
July 2013.
Keywords: Range management -- Colorado -- Pueblo County; Vegetation surveys -- Colorado -- Pueblo County